2016
DOI: 10.1098/rsbl.2016.0503
|View full text |Cite
|
Sign up to set email alerts
|

Changes in composition and abundance of functional groups of arctic fungi in response to long-term summer warming

Abstract: We characterized fungal communities in dry and moist tundra and investigated the effect of long-term experimental summer warming on three aspects of functional groups of arctic fungi: richness, community composition and species abundance. Warming had profound effects on community composition, abundance, and, to a lesser extent, on richness of fungal functional groups. In addition, our data show that even within functional groups, the direction and extent of response to warming tend to be species-specific and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 18 publications
2
23
1
Order By: Relevance
“…Furthermore, habitat‐scale filters likely drive the establishment of a further subset of the local species pool, partly selected according to their functional attributes. Similar to Geml, Semenova, Morgado, and Welker (), we also observed compositional differences amongst habitats within the functional groups (Figure ). This suggests that at a habitat scale, within‐group functional variability (e.g., differences in nutrient acquisition or contrasting types of hyphal exploration) may influence species composition in relatively stable, climax communities by niche‐based rather than stochastic processes that are more common in early successional stages (Blaalid et al., ; Jumpponen, ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, habitat‐scale filters likely drive the establishment of a further subset of the local species pool, partly selected according to their functional attributes. Similar to Geml, Semenova, Morgado, and Welker (), we also observed compositional differences amongst habitats within the functional groups (Figure ). This suggests that at a habitat scale, within‐group functional variability (e.g., differences in nutrient acquisition or contrasting types of hyphal exploration) may influence species composition in relatively stable, climax communities by niche‐based rather than stochastic processes that are more common in early successional stages (Blaalid et al., ; Jumpponen, ).…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have experimentally demonstrated that the composition and function of fungal communities shift in response to increased snow accumulation or temperature (Deslippe, Hartmann, Simard, & Mohn, ; Geml et al., , ; Morgado et al., , ; Mundra et al., ; Semenova et al., , ). However, further investigations are needed, since complex interactions may occur with habitat type (Morgado et al., ), changes in N deposition (Lilleskov et al., ), date of snowmelt (Schmidt et al., ), microbial activity in winter (Aanderud, Jones, Schoolmaster, Fierer, & Lennon, ; Buckeridge & Grogan, ; Schimel, Bilbrough, & Welker, ; Semenchuk et al., ), floristic composition or climatic variability.…”
Section: Discussionmentioning
confidence: 99%
“…Biological drivers potentially tied to fluxes are improved species performance [ Chapin and Shaver , ; Oberbauer et al, ], shift in plant communities [ Walker et al , ; Schuur et al , ; Myers‐Smith et al , ; Hollister et al , ], and herbivory [ Welker et al , ; Kelsey et al , ]. The warming of soils and thawing of permafrost stimulate soil organic matter decomposition [ Mackelprang et al , ; Schädel et al , ; Xue et al , ] and increase heterotrophic respiration from soils result in a positive feedback to the atmospheric CO 2 concentration but will depend on snow accumulation [ Nowinski et al , ; Blanc‐Betes et al , ] and changes in soil community abundance and composition [ Mohan et al , ; Morgado et al , ; Parker et al , ; Semenova et al , ; Geml et al , ; Morgado et al , ]. Increased CO 2 loss may, however, be counteracted by increases in net primary production (NPP) as plant productivity increases [ Epstein et al , ] and the plant community shifts from graminoid to shrub dominance [ Sturm et al , ; Walker et al , ; Myers‐Smith et al , ; Pearson et al , ; Hollister et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, increasing diversity of the flora in the European tundra as a whole and those specific local floras are more obvious here compared to continental regions of Siberia (Yurtsev et al 2004; Walker et al 2012; Belonovskaya et al 2016). Traditionally, these processes are studied on the basis of various groups of animals and plants, whereas representatives of the Fungi Kingdom are extremely uncommon to be used as model groups (Dahlberg et al 2013; Geml et al 2016). …”
Section: Introductionmentioning
confidence: 99%